2020
DOI: 10.15761/prr.1000130
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture point injection with placental extract improves pain and quality of life in patients with fibromyalgia syndrome

Abstract: Context: Fibromyalgia syndrome (FMS) can seriously affect the quality of patient lives due to chronic widespread pain. One of treatment strategies for the management of FMS is complementary and alternative medicine (CAM) treatments including acupuncture. A new acupuncture therapy, acupuncture point injection (API) that combines acupuncture and medication is recently used in China and Korea to accomplish more effective therapeutic outcomes. Yet, there is no attempt to investigate the effect of API with placenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…PE was verified to decrease symptoms of fatigue and increase the resistance to physical stress in animals and humans [2,12]. Besides, we observed the acupuncture point injection of PE ameliorated pain and quality of life in knee arthritis and FMS patients [1,13]. Studies in FMS patients demonstrated that chronic persistent pain, poor sleep quality, depressed mood, anxiety, and combinations of these were associated with fatigue [14,15].…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…PE was verified to decrease symptoms of fatigue and increase the resistance to physical stress in animals and humans [2,12]. Besides, we observed the acupuncture point injection of PE ameliorated pain and quality of life in knee arthritis and FMS patients [1,13]. Studies in FMS patients demonstrated that chronic persistent pain, poor sleep quality, depressed mood, anxiety, and combinations of these were associated with fatigue [14,15].…”
Section: Discussionmentioning
confidence: 71%
“…Its pathophysiology still remains a mystery. Diverse treatment strategy including pharmacological therapies, non-pharmacological conventional therapies, and complementary and alternative medicine therapies has been used for the management of FMS.Previously, we reported acupuncture point injection of placenta extract (PE) in FMS patients relieved pain, ameliorated sleep disorder, and increased daily productive time [1].Experimental studies on the effect of PE on behavior and physical condition in the animal model showed decrease in symptoms of fatigue and increased resistance to physical stress [2].…”
Section: Introductionmentioning
confidence: 99%